AN ANALYSIS OF LEXICAL COHESION FOUND IN “NEVER SAY NEVER” SONG LYRICS - Pratiwi, Vivi Yulia; Jayanti, Yeni Dwi; Syathroh, Isry Laila (IKIP Siliwangi, 2019)
The purpose of this study is to describe kinds of lexical cohesion and to know frequent lexical cohesion used to support the cohesiveness of discourse in Justin Bieber and Jaden Smith’s song entitled “Never Say Never”. The subject of this study is “Never Say Never” song lyrics. This study uses descriptive qualitative that focuses on lexical cohesion in particular synonym, repetition (anaphora and epistrophe repetition) and antonym. The instrument that the researchers used are books, earphone, youtube and other supporting tools. From this study, the result shows that the lyrics of “Never Say Never” song contains eleven forms of lexical cohesion, consisting of two synonyms, seven repetitions, and two antonyms. So the most frequent occurrence in the data is repetition. The function of lexical cohesion is to make the lyrics have harmonization that makes the lyrics more meaningful